SOME FELLER SEMIGROUPS ON $C_{∞ }(\mathbb{R}^{n}× \mathbb{Z}^{m})$ GENERATED BY PSEUDO-DIFFERENTIAL OPERATORS. Issue 2 (15th April 2015) - Evans, Kristian P.; Jacob, Niels; Shen, Chenglin
Abstract : In this paper we construct some Feller semigroups, hence Feller processes, with state space $\mathbb{R}^{n}× \mathbb{Z}^{m}$ starting with pseudo-differential operators having symbols defined on $\mathbb{R}^{n}× \mathbb{R}^{n}× \mathbb{Z}^{m}× \mathbb{T}^{m}$ .